2008
DOI: 10.1128/iai.00552-08
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Are Locally Induced during Intravaginal Infection of Mice withNeisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae is a gram-negative diplococcus that in human beings produces gonorrhea. Much clinical evidence has led to the conclusion that gonococcus has important mechanisms to evade host immune functions; however, these mechanisms are only now beginning to be elucidated. In this study, we determined that the BALB/c mouse is a good animal model to study gonococcus infection and examined the immune response against the bacteria. We determined that after intravaginal inoculation of mice with Neisseria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…N. gonorrhoeae also cannot use murine lactoferrin or transferrin as sources of iron (14,43), and the gonococcal immunoglobulin A1 (IgA1) protease cannot cleave mouse IgA (40). Despite these host restrictions, studying gonococcal pathogenesis in the murine model has yielded considerable insight into the host response to infection (25,31,58,76) and the role of certain gonococcal virulence factors in evasion of host defenses (34,75,81,84,85). The mouse model has also allowed the demonstration of hormonal (13,32,73), as well as the effect of certain antibiotic resistance mutations on microbial fitness (82).…”
Section: Discussionmentioning
confidence: 99%
“…N. gonorrhoeae also cannot use murine lactoferrin or transferrin as sources of iron (14,43), and the gonococcal immunoglobulin A1 (IgA1) protease cannot cleave mouse IgA (40). Despite these host restrictions, studying gonococcal pathogenesis in the murine model has yielded considerable insight into the host response to infection (25,31,58,76) and the role of certain gonococcal virulence factors in evasion of host defenses (34,75,81,84,85). The mouse model has also allowed the demonstration of hormonal (13,32,73), as well as the effect of certain antibiotic resistance mutations on microbial fitness (82).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the role of regulatory T (Treg) cells, we showed that in Balb/c, the mouse model of gonococcus infections, N. gonorrhoeae induces transforming growth factor 1 (TGF-1)+ CD4 + T cells in the mucosal lymph nodes, including a subset of CD25+Foxp3+ Tregs, indicating that type of response may avoid the host mechanisms of protection (Imarai et al, 2008). Mature CD4+ CD25-T cells can be converted in Treg cells in peripheral tissues under immunosuppressive conditions, such as exposure to IL-10 or TGF-1 made by antigen presenting cells (Sakaguchi, 2004).…”
Section: Mechanisms Of Immune Evasion By Neisseria Gonorrhoeaementioning
confidence: 99%
“…Interestingly, studies in this model revealed several features of infection that mimic a good spectrum of the characteristics of the human disease. Some of them seem highly valuable, (i) the bacteria introduced in the vagina not only invade and colonize the lower genital tract, but also spread to the upper organs (uterus and oviducts) , (ii) infection occurs with no signs of the disease, just as it occurs in a high percentage of women during natural infection (Farley et al, 2003;Inaba et al, 1992) and (iii) the bacteria remains alive within the internal compartments of the infected cells, invading uterine tissues up to 22 days post inoculation (Imarai et al, 2008).…”
Section: N Gonorrhoeae Mice Infectionmentioning
confidence: 99%
See 2 more Smart Citations